(untitled) (Revista do CAAP, 2024)
Resumo: O presente trabalho pretende analisar a norma contida no art. 1641, II do Código Civil e a adoção do critério biológico puro ou critério etário enquanto fator determinante da presunção absoluta de incapacidade do idoso de escolher o regime de bens de seu matrimônio. Objetiva contextualizar a norma estudada com os aspectos sociais que fundamentaram sua criação, bem como abordar de forma crítica as incongruências que a aplicação do regime de separação obrigatória de bens gera no ordenamento jurídico brasileiro, propondo, por fim, uma solução adequada de alteração do art. 1641, II do Código Civil, através da criação de um procedimento na fase de habilitação do casamento, que permita extirpar as inconstitucionalidades do atual sentido da norma e a incompatibilidade do seu conteúdo com demais dispositivos e princípios do ordenamento jurídico brasileiro, sem desproteger aquele septuagenário que efetivamente demonstre vulnerabilidade. Palavras-chave: Código Civil. Direito de Família. Regime de separação obrigatória de bens.Inconstitucionalidade. A new proposal concerning the property regime of compulsory separation of septuagenarians. Abstract: The present work aims to analyze the norm contained in the article 1641, II of the Civil Code and the adoption of the pure biological criterion or the age criterion as determinant factor of the absolute presumption of incapacity of the elderly to choose the marital property regime. Also, this work objectifies to contextualize the studied norm with the social aspects that motivated its creation, as well as intends to critically broach the incongruities that the application of the compulsory separation marital property regime generates in the Brazilian legal order, finally proposing an appropriate amendment of the article 1641, II of the Civil Code, by creating a procedure in the certifying phase of marriage, that allows to extirpate the unconstitutionalities of the current sense of the norm and the incompatibility of its content with other provisions and principles of legal system, without unprotecting the septuagenarian that indeed demonstrates vulnerability. Keywords: Civil Code. Family Law. Compulsory separation property regime. Unconstitutionality.